Microbiological analysis of critical points in the chicken industry - Cansian,Rogério Luis (2005)
This work is focused on identifying microbial contamination in the scalding asepsis and cooling processes as well as in fresh sausages obtained. Salmonella was identified in two scald water samples but was absent in the water from chiller and in the final product, which might be explained in terms of chlorine addition and temperature reduction. The analysis revealed that MPN of Escherichia coli was in the range of <1-11/mL in the scald water and <1-64/mL in the chiller. Aeromonas sp. count showed 5 to 3.5x10¹ CFU/mL in the scald water and 9 to 3.7x10² CFU/mL in the chiller, probably due to the psycrophile characteristics of Aeromonas and evisceration process. The analysis of fresh sausages chicken revealed a sharp increase in the Aeromonas count (2.5x10³ CFU/g). Results showed the need of including Aeromonas analyzes in microbiological tests of foods.